2020
DOI: 10.1002/adem.202000134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preannealing on Microstructural Evolution and Tensile Properties of a Novel Nickel‐Based Superalloy

Abstract: Nickel-based superalloys are widely applied in aeronautical, aerospace, nuclear, and petrochemical industries, due to their excellent high-temperature mechanical properties. [1-3] Disc superalloys, such as Allvac 718Plus, [4] Waspaloy, [5] FGH100L, [6] and GH4065, [7,8] are the typical representatives of nickel-based superalloys for the critical rotating components of aircraft engines and gas turbines. The nickel-based alloy GH4065 developed for aerospace turbine disc superalloys is strengthened by gamma prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…To meet the need of turbine disks in the next-generation engine, several novel superalloys have been developed in previous studies, such as Allvac 718Plus, [7] Udimet 720Li, [8,9] AD730, [10] FGH100L, [11] GH4151, [12] and GH4065. [13,14] GH4065 alloy, a novel cast and wrought (C and W) superalloy, was developed as a highly alloyed γ-γ 0 nickel-based superalloy used for turbine disks superalloy at a service temperature up to 750 C. Due to its excellent high-temperature performance, GH4065 is widely applied to hot components of aeroengines. The alloy has been one of the optimized materials for critical rotating components, such as turbine disks and blades, in the range of 700-750 C for high-performance aeroengines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the need of turbine disks in the next-generation engine, several novel superalloys have been developed in previous studies, such as Allvac 718Plus, [7] Udimet 720Li, [8,9] AD730, [10] FGH100L, [11] GH4151, [12] and GH4065. [13,14] GH4065 alloy, a novel cast and wrought (C and W) superalloy, was developed as a highly alloyed γ-γ 0 nickel-based superalloy used for turbine disks superalloy at a service temperature up to 750 C. Due to its excellent high-temperature performance, GH4065 is widely applied to hot components of aeroengines. The alloy has been one of the optimized materials for critical rotating components, such as turbine disks and blades, in the range of 700-750 C for high-performance aeroengines.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the need of turbine disks in the next‐generation engine, several novel superalloys have been developed in previous studies, such as Allvac 718Plus, [ 7 ] Udimet 720Li, [ 8,9 ] AD730, [ 10 ] FGH100L, [ 11 ] GH4151, [ 12 ] and GH4065. [ 13,14 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, next generation engines are increasingly demanding, and a higher temperature capacity of turbine disks is required in order to improve the engine performance. Traditionally used alloys, such as Inconel 718 (limited to 650 °C) [ 3 ], 718Plus (limited to 710 °C) [ 4 ], Udimet 720Li (limited to 730 °C) [ 5 , 6 ], GH4065 [ 7 ], and AD730 (limited to 750 °C) [ 8 ] are already pushed towards their limits in view of the stability of the microstructure and mechanical properties, resulting in the development of an advanced nickel-based superalloy.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this objective, next-generation polycrystalline γ-γ 0 nickel-based superalloys are newly developed for turbine disks at service temperatures up to 750 °C. [6,7] Especially for the newly developed disk superalloys, it is essential to have a better understanding of creep deformation mechanisms under their service conditions.Generally, the creep performance depends on deformation parameters, such as temperature, stress, strain, and microstructure, which have been investigated by several groups. Viswanathan et al [9] studied that creep deformation mechanisms at 650 °C/(790-972 MPa) in René 88DT and demonstrated that the transition of creep mechanism from micro-twinning to shearing by 1/2[110] dislocations and Orowan looping around the larger secondary precipitates when lower applied stress change to higher applied stress.…”
mentioning
confidence: 99%
“…To achieve this objective, next-generation polycrystalline γ-γ 0 nickel-based superalloys are newly developed for turbine disks at service temperatures up to 750 °C. [6,7] Especially for the newly developed disk superalloys, it is essential to have a better understanding of creep deformation mechanisms under their service conditions.…”
mentioning
confidence: 99%